2015
DOI: 10.1080/02673843.2014.996236
|View full text |Cite
|
Sign up to set email alerts
|

Grade point average and biographical data in personal resumes: predictors of finding employment

Abstract: This study aimed to examine relationships between graduates' grade point average (GPA), biographical data and success in finding a job in general and a psychologybased job in particular. Two hundred six psychology graduates participated in a twowave longitudinal study. Biographical data assessed were extracurricular activities, computer and foreign language skills, participation in a growth mindset enrichment programme and in general enrichment programmes, and work experiences. GPA showed significant relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Food‐insecure students had a slightly lower GPA than food‐secure students, which was evident even in the ZOIB regression that controlled for other predictors of GPA such as high school academic performance (as measured by Colorado Index) and socioeconomic background (as measured by Pell Grant status). As GPA is seen as an indicator of academic success and can influence future employment (Nunley et al, ; Sulastri et al, ), this is a significant finding. An estimate of the impact of food insecurity on GPA can be obtained from the estimated model by assuming food‐insecure students were food secure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food‐insecure students had a slightly lower GPA than food‐secure students, which was evident even in the ZOIB regression that controlled for other predictors of GPA such as high school academic performance (as measured by Colorado Index) and socioeconomic background (as measured by Pell Grant status). As GPA is seen as an indicator of academic success and can influence future employment (Nunley et al, ; Sulastri et al, ), this is a significant finding. An estimate of the impact of food insecurity on GPA can be obtained from the estimated model by assuming food‐insecure students were food secure.…”
Section: Discussionmentioning
confidence: 99%
“…Colorado Index) and socioeconomic background (as measured by Pell Grant status). As GPA is seen as an indicator of academic success and can influence future employment (Nunley et al, 2016;Sulastri et al, 2015), this is a significant finding. An estimate of the impact of food insecurity on GPA can be obtained from the estimated model by assuming food-insecure students were food secure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may have implications for academic performance and future well-being, because better executive function may offer an edge in a competitive academic environment and because performance in college has been shown to relate to future employment (44). Although most work to date on the topic of fitness and cognition has been done in children and older adults, this study adds to the available evidence of such a relation in younger adults.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, it has been shown that it is important to include work experience information even if the previous experience is unrelated to the job in question (Hornsby & Smith, 1995;Sulastri, Handoko, & Janssens, 2015).…”
Section: Work Experiencementioning
confidence: 99%